Treatment of acidic wastewater from thien ke tin processing factory by sulfate reducing bioreactor: a pilot scale study - Hai, Nguyen Thi; Hang, Dinh Thuy (Vietnam Journal of Biotechnology, 2018)
A pilot-scale system of a total volume of 6 m3 using sulfate reducing (SR) bioreactor technology was established for the treatment of acidic wastewater from Thien Ke tin processing factory in Tuyen Quang province, Vietnam. In the system, the acidic wastewater with high metal content went first to a collecting tank filled with limestone gravels to increase pH to a value favorable for SRB growth, and at the second step to a SR bioreactor where sulfate reduction occurred to produce sulfide for metal precipitation. To activate the SR bioreactor, a laboratory SRB mixed culture dominated by Desufovibiro, Desulfobulbus and Desulfomicrobium species was added at a cell density of 106 cell/ml so that a full activation was achieved just after a week of incubation. Molasses was added to the SR bioreactor at 0.5 ml/L as substrate for the SRB growth during the operation. The performance of the system was studied under batch and continuous modes. The batch mode showed good results after three day-operation. The pH increased from 2.8 – 3.2 to 7 – 7.2, and a total of 750 mg/L sulfate was reduced to sulfide presumably by the SRB. The produced sulfide efficiently removed metals from the wastewater, such as iron from 143.1 mg/L to 0.3 mg/L, copper from 16.32 mg/L to 0.04 mg/L and manganese from 10.9 mg/L to 0.05 mg/L. The continuous mode with a hydraulic load of 100 l/h and an according retention time of three days showed constitutive contaminant removal. The effluent pH of the system was around 7 within six-day period. The sulfate reduction was active, keeping sulfate concentration in the final effluent as low as  150 mg/L. Accordingly, the three most metal contaminants (iron, copper and manganese) were found at concentrations below the regulated limits. The results showed the possibility of applying SR bioreactor technology for the treatment of AMD is feasible and the use of previously enriched mixed culture of SRB could be a good approach to shorten the activation period of the SR bioreactor